2016
DOI: 10.1073/pnas.1611496113
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of light-driven, concerted electron–proton transfer

Abstract: The phenols 4-methylphenol, 4-methoxyphenol, and N-acetyl-tyrosine form hydrogen-bonded adducts with N-methyl-4, 4′-bipyridinium cation (MQ+) in aqueous solution as evidenced by the appearance of low-energy, low-absorptivity features in UV-visible spectra. They are assigned to the known examples of optically induced, concerted electron–proton transfer, photoEPT. The results of ultrafast transient absorption measurements on the assembly MeOPhO-H---MQ+ are consistent with concerted EPT by the instantaneous appea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 52 publications
5
29
0
Order By: Relevance
“…Additionally, phenol–imine excited states often exhibit emission in the visible range, 36 but photoexcited samples of 1H showed emission only from anthracene, suggesting that phenol–imine excited states were not present and energy transfer did not occur. The data presented here, together with published results on bimolecular oxidations of similar phenol–base compounds (including with excited anthracene), 3,4,725 all indicate the MS-CPET mechanism in Scheme 1.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…Additionally, phenol–imine excited states often exhibit emission in the visible range, 36 but photoexcited samples of 1H showed emission only from anthracene, suggesting that phenol–imine excited states were not present and energy transfer did not occur. The data presented here, together with published results on bimolecular oxidations of similar phenol–base compounds (including with excited anthracene), 3,4,725 all indicate the MS-CPET mechanism in Scheme 1.…”
supporting
confidence: 79%
“…5 Experimental studies of MS-CPET in hydrogen-bonded phenol-base systems have shown that MS-CPET rates vary with the driving force, Marcus-type intrinsic barriers, and electron and proton donor–acceptor distances. 3,4,725…”
mentioning
confidence: 99%
“…A recent review on excited sate [Ru(bpy) 3 ] 2+ by Meyer et al. emphasizes on MLCT and electronic configuration in excited state . PCET between phenol and [Ru(bpy) 3 ] 2+ at low pH with stepwise electron transfer proton transfer (ETPT) correlating with Marcus type driving force has been reported by Hammarstrom and coworkers .…”
Section: Introductionmentioning
confidence: 98%
“…Majority of the work has been carried out on ground state PCET, also referred as thermal‐PCET . Thermal PCET can occur either by stepwise electron transfer followed by proton transfer or vice‐versa (ET‐PT or PT‐ET) or in a concerted single step electron and proton transfer (CEPT) pathway . The excited state PCET (ES‐PCET) though less explored, have potential applications in solar fuel production and small molecule activation.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16] Given the relevance of this process and the complexity of such ultrafast measurements, theoretical approaches are needed to model the electronic structure of the involved chromophore, its nuclear and electronic photodynamics, and their manifestation in the spectro-scopic observables. In particular, since the migrating proton can undergo tunneling and nonadiabatic effects might be operative, [16][17][18][19] it is crucial to develop computational strategies where at least the H atom motion is treated quantum mechanically. [20][21][22][23] A prototypical molecule to investigate ultrafast ES-IPT and explore the potentialities of new spectroscopic techniques is 10-hydroxybenzo[h]quinoline (HBQ), which undergoes the enol to keto photoisomerization depicted in Fig.…”
Section: Introductionmentioning
confidence: 99%